Effect of the vertical stress on CO2 flow behavior and permeability variation in coalbed methane reservoirs. Issue 5 (7th July 2019) - Ding, Ziwei; Jia, Jindui; Feng, Ruimin
Abstract: Given that in situ stress evolution is of great importance in characterizing coalbed methane reservoirs during gas production, CO2 sequestration, and reservoir fracturing, a series of laboratory measurements were conducted to investigate the role of the vertical stress on gas flow behavior and permeability evolution of San Juan Basin coal. Due to the difficulty in maintaining a steady‐state flow when testing coals with tight structure, the pressure transient technique was employed and experiments were conducted under different boundary conditions: uniaxial strain condition and lateral stress‐controlled condition. The results indicated that the vertical stress has a negative role in permeability enhancement. To verify this finding, one more set of experiments under the vertical stress‐controlled condition was carried out. In addition, the application of CO2 injection on reservoir fracturing was theoretically analyzed. The results indicated that both CO2 injection and the vertical stress can exert positive effects on reservoir fracturing. This study contributes to the understanding of the effect of the vertical stress on permeability variation during CO2 injection, which has practical significance for permeability modeling and reservoir fracturing operation in the field. Abstract : Vertical stress is experimentally verified to play a negative role in permeability enhancement. Mohr's circle of strain can be readily used for analyzing deformation behavior of coalbed reservoirs. CO2 can be used as a pretreatment fluid and exert positive effects on improving the effectiveness of reservoir fracturing.